Identification of Phosphoprotien : Phosphoprotien and Phosphoprotien : Nucleocapsid Protein Interaction Domains of New Castle Disease Virus - Jahanshiri, Fatemeh; Eshaghi, Majid; Yusoff, Khatijah (Springer Wien, 2004)
Summary : The yeast two hybrid system has been used to identify domains of the Newcastle disease virus ( NDV ) phosphoprotien (P) involved in self –association and interaction with the nucleocapsid protein (NP). Deletion analysis was used to map the domain (s) of the P protein involved in P:P and P:NP interactions. The C- terminal 45 amino acids (residues 247-291) were shown to play a major role in both of interaction. Comparison of these finding with other report suggests that paramyxoviruses are different with respect to interaction domain(s) between these two essential viral proteins involved in genome replication.